Estetika Gaya Bahasa dan Simbol dalam Geguritan "Dom" dalam Antologi Mendut-mendut Karya R. Djoko Prakoso - Ro’Aida Nur Aini; Ucik Faudhiyah; Sucipto Hadi Purnomo (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
Geguritan is a form of modern Javanese poetry that utilizes the beauty of language and symbols to convey inner experiences and life values. The geguritan anthology Mendut-mendut by R. Djoko Prakoso is rich in aesthetic and symbolic elements that are worth studying, particularly in the geguritan titled “Dom”. This study aims to describe the aesthetics of stylistic language and symbols in the geguritan “Dom”. The study employs a qualitative descriptive method using a stylistic and semiotic approach. The research data consist of words, phrases, lines, and stanzas containing aesthetic elements of stylistic language and symbolism in Dom’s geguritan. Data were collected through documentation and literature review, then analyzed descriptively. The results of the study indicate that the aesthetics of the geguritan are constructed through the use of connotative diction, metaphors, imagery, repetition, and wordplay, which shape aesthetic and emotional experiences. Additionally, symbols such as night, heart, eyes, soul, torch, pancer, and seed were identified, representing longing, love, loss, hope, reflection, and the process of inner maturation. The findings indicate that stylistic and semiotic aspects complement one another in constructing the depth of meaning and artistic value of geguritan. It is hoped that these findings will serve as a reference for the development of Javanese literary studies, particularly research on the aesthetics of stylistic features and symbols in modern geguritan.